(untitled) (Future Cities and Environment, 2024)
The wastewater from the textile industry generally contains toxic chemicals methylene blue that are difficult to degrade by the environment. This study aims to develop a high-performance natural photocatalyst from Bentonite impregnated by N-TiO2 with a high photodegradation rate for methylene blue removal under UV and visible light. Characterization of the material was conducted using SEM-EDX, XRD, and FTIR. The EDX results showed that elemental N had been detected in N-TiO2 and N-TiO2/activated bentonite. The FTIR spectra showed that the absorption peak of N-TiO2/activated bentonite is similar to that of activated bentonite and N-TiO2. The N-TiO2/activated bentonite diffractogram showed the peaks of quartz and montmorillonite minerals. The N-TiO2/activated bentonite photocatalyst resulted in a decrease in the bandgap energy of 3.06 eV. The decline in band gap energy on N-TiO2/activated bentonite is higher than the decrease in band gap energy for N-TiO2. The optimum pH condition for the photocatalyst process in removing methylene blue occurs at pH 5. The maximum removal efffciency of methylene blue occurs when the ratio of N: Ti is 1:1 with an irradiation time under UV and visible lights of 120 minutes of 99.23% and 87.20%, respectively. This study showed that the composite catalyst N-TiO2/bentonite under UV and visible light irradiation conditions has higher removal efficiencies on lower dosages (2.5–10 times lower in dosage), higher initial methylene blue concentration (1.25–2.5 times higher in concentration), and shorter reaction (1.5–3 times shorter in irradiation time) than composite catalysts from previous studies’ results. Furthermore, the product can enhance the value of local natural bentonite and increase local people’s income and welfare.